Binge drinking in young adolescents was associated with the consumption of alcoholic beverages by family members and best friends? - Paiva, Haroldo Neves de (2023)
An important risk factor is alcohol consumption, with the most used psychotropic drug among adolescents. Objective was to evaluate prevalence of binge drinking in 14-year- olds and association with alcohol drinking by family members and best friend. Cross-sectional study of population base using the Audit-C instruments and semi-structured questionnaire to evaluate alcohol consumption. The data were analyzed descriptively and analytically (p<0.05). The prevalence of drinking binge was 23.1%. Considering the alcohol drinking by parents and friends, it was found that the fact that the mother, father, brother and best friend drink were associated with binge in drinking by adolescents (p=0.001, p<0.0001, p<0.0001, p<0.0001) respectively. The binge drinking was considered high, early onset and was associated with alcohol consumption by the best friend and the best friend.